2022
DOI: 10.1097/prs.0000000000009799
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dose and Injection Site on Gingival Smile Treatment with Botulinum Toxin Type A: A Prospective Study.

Abstract: he smile is one of the universal facial expressions of humans. Gingival smile is characterized by gingival exposure of greater than 3 mm when smiling. The degree of gingival exposure can vary substantially between patients, with patients presenting gingival exposure of up to more than 10 mm. 1,2 The prevalence of gingival smile is 10.57%, 3 and it is more frequently observed in female patients. 4,5 Although gingival smile is merely an anatomical variation, it can be considered unattractive, causing significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(70 reference statements)
1
7
0
Order By: Relevance
“…Next, the authors concluded that increasing the number of injection points (in G1 vs G2) did not improve the clinical result but did increase the longevity of the clinical effect of botulinum toxin on EGD. This was in line with Nasr et al's conclusions from a recent systematic review, 3 which is not too dissimilar from a recent study by Gong et al 4 Interestingly, Gong et al also compared 2 injection points similar to those in the current study, at the LLSAN and Yonsei point. Although the authors should be commended on their efforts to perform electromyography (EMG) as a means to evaluate the perioral musculature after treatment of EGD with botulinum toxin, as they have alluded to themselves, however, “EMG captures the electrical activity of a region and not only of the LLSAN and LLS muscles, which might be the case here,” 1 and this can be seen in Table 4, where the results are difficult to interpret (for instance, was the increase from 125 to 169 Aa at Week 16 due to a different operator, since it went back down to 125 at Week 21?…”
supporting
confidence: 93%
“…Next, the authors concluded that increasing the number of injection points (in G1 vs G2) did not improve the clinical result but did increase the longevity of the clinical effect of botulinum toxin on EGD. This was in line with Nasr et al's conclusions from a recent systematic review, 3 which is not too dissimilar from a recent study by Gong et al 4 Interestingly, Gong et al also compared 2 injection points similar to those in the current study, at the LLSAN and Yonsei point. Although the authors should be commended on their efforts to perform electromyography (EMG) as a means to evaluate the perioral musculature after treatment of EGD with botulinum toxin, as they have alluded to themselves, however, “EMG captures the electrical activity of a region and not only of the LLSAN and LLS muscles, which might be the case here,” 1 and this can be seen in Table 4, where the results are difficult to interpret (for instance, was the increase from 125 to 169 Aa at Week 16 due to a different operator, since it went back down to 125 at Week 21?…”
supporting
confidence: 93%
“…The initial severity of gingival exposure and the treatment modality played a role in the treatment effects. Gong et al (2023) categorized the pre-treatment gingival show into three groups based on severity: mild (3–5 mm), moderate (5–7 mm), and severe (greater than 7 mm) [ 39 ]. In this meta-analysis, the studies were divided into three groups based the range of initial EGD: mild (2–3.99 mm), moderate (4–5.99 mm), and severe (6 mm or more).…”
Section: Discussionmentioning
confidence: 99%
“…The nonsurgical studies included BTX injection and orthodontic intrusion. The studies were further subdivided into three groups based the range of initial EGD: mild (2–3.99 mm), moderate (4–5.99 mm), and severe (6 mm or more) [ 3 , 39 , 40 , 41 ]. The post-treatment changes in gingival display at four time points (1, 3, 6, and 12 months) were calculated, pooled by using a random-effects model, and expressed as mean difference with a 95% confidence interval (CI) using a single-cohort meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,11,12,18,35,36 According to our recent findings, 3 U per side is suitable for a gummy smile with the anterior GE less than 5 mm, but is not sufficient for GE of 5 mm or greater. 37 Thus, further research will be designed to explore injection doses for more appropriate treatment for gummy smile.…”
Section: Discussionmentioning
confidence: 99%